Hemodynamic causes in cerebrovascular ischemic event - Quistapace, María Soledad; Zurrú, María Cristina (Revista del Hospital Italiano de Buenos Aires, 2015)
Hemodynamic stroke is a poorly described entity. It can be caused by systemic diseases such as heart failure or hypotension, but also by severe obstruction of the carotid or vertebral arteries. Patients with hemodynamic cerebrovascular event might show specific clinical features that distinguish them from patients with embolism or local small-vessel disease. Complementary studies of cerebral perfusion can show whether blood flow to the brain is compromised and provide important prognostic information. Treatment aimed at increasing cerebral blood flow might be considered in patients with severa extracraneal artery stenosis on the basis of information from case series